Contradictory individualized self-blaming: a cross-sectional study of associations between expectations to managers, coworkers, one-self and risk factors for musculoskeletal disorders among construction workers. Issue 1 (December 2017) - Ajslev, Jeppe; Persson, Roger; Andersen, Lars
Abstract Background Within work sociology, several studies have addressed construction workers' practices of masculinity, class, economy, safety risks and production. However, few studies have investigated room for agency in relation to bodily pain or musculoskeletal disorders and even fewer have made a quantitative approach. Accordingly, by means of a questionnaire, we examined the association between construction workers' room for agency and physical exertion, bodily and mental fatigue, and lower back pain. Methods A total of 481 Danish construction workers who responded to a multifaceted questionnaire were included. Drawing on previous studies and a Foucauldian inspired concept of agency, agency was quantified through specially crafted questions and examined in relation to established measures on physical exertion, physical and mental fatigue and pain in the lower back. Associations were tested using analyses of variance (general linear models) and controlled for age, gender, job group, lifestyle and depression. Results When asked about options for agency reducing the burden of work, few workers believed themselves to be prime agents of such practices. When asking about their view on performing alternative agency implying caring for the body, 39–49% expected negative reactions from management, and 20–33% expected negative reactions from colleagues. In contrast, only 13–18% of the participants stated that they would give a negative reception to such alternative practices. Using the expected reception outcomes (positive, neutral, negative) to alternative practices as predictors, the statistical regression analyses showed that negative expectations to management were associated with higher levels of physical exertion 0.62 (95% CI = 0.14–1.09) (scale 0-11), bodily fatigue 0.63 (95% CI = 0.22–1.04), mental fatigue 0.60 (95% CI = 0.07–1.12), and low back pain 0.79 (95% CI = 0.13–1.46) (scales 0-10). Conclusion In our study, construction workers answered questions about work and MSD. The answers indicated a contradiction between perceived responsibility and room for agency. Based on the study, a number of target areas could fruitfully be addressed in aiming to reduce MSD among construction workers. To change workers' expectances to the reception of lowering work pace if needed to take care of the body, their expectances to the reception of sickness absence as a result of pain, of discussing physical exertion in work and of demanding appropriate technical assistive devices are such examples. Our results emphasize that management plays an important role in this.